EFL TEACHERSâ TEACHING STRATEGIES IN PUBLIC VOCATIONAL HIGH SCHOOLS IN SINGARAJA - ., Nurul Inayah (Jurnal Pendidikan Bahasa, 2012)
ABSTRACTÂ This research was conducted in an attempt to investigate the EFL teachersâ teaching strategies in Public Vocational High Schools in Singaraja. It is concerned with what teaching strategies implemented by the EFL teachers, similarities and differences of teaching strategies applied, and problems encountered by the teachers in implementing the strategies. The settings of this research were three Public Vocational High Schools in Singaraja, namely: SMKN 1 Singaraja, SMKN 2 Singaraja, and SMKN 3 Singaraja. The subjects of this research were six EFL teachers who taught Tenth Grade students. This research was designed as a qualitative research. The data were collected through questionnaire, interview, observation, and document study. Data were analyzed by using Celce-Murcia (2001) and Herrel and Jordan (2004) EFL teaching strategies. Based on the data analysis, the study identified some findings. First, the EFL teachers in Public Vocational High Schools in Singaraja implemented various teaching strategies. There were approximatelyÂ  thirty four strategies were implemented, namely: Academic language Scaffolding, Advance organizers, Language focus lessons, Cloze, Collaborative reading, Communication games, Cooperative learning, Emotive writing tasks, Guided writing, Imaging, Interactive listening, Attribute charting, Language framework planning, Learning centers, Leveled questions, Listening and answering, Listening and repeating, Modeled talk, Multimedia presentations, Part-centered, Partner work, Peer Tutoring, Practical writing tasks, Predictable routines and signals, Realia strategies, Scripting, Socio-psycholinguistic, Sorting activities, Task listening, Visual scaffolding, Vocabulary processing, Vocabulary role play, Talk show, and Syntax surgery. Second, there were strategies which were similar from one school to the others with similarities or differences in the focused of the skills and also the procedures in applying the strategies. It was also found that the number of strategies implemented in the three schools was different. Third, there were some problems that the EFL teachers dealt with in implementing the strategies. They were the students, in terms of their level, motivation and heterogeneity, the teachers, in terms of their lack of motivation to teach and their personality, and the facility. Â  Key words: teaching strategy, Public Vocational High SchoolÂ ABSTRAKÂ Penelitian ini bertujuan untuk meneliti strategi pembelajaran guru Bahasa Inggris di SMK Negeri di Singaraja, khususnya jenis-jenis strategi pembelajaran yang digunakan, persamaan dan perbedaan strategi yang digunakan di SMK Negeri di Singaraja, dan masalah yang dihadapi dalam pelaksanaan strategi. Penelitiam dilakukan di tiga SMK di Singaraja, SMKN 1 Singaraja, SMKN 2 Singaraja, and SMKN 3 Singaraja. Subjek penelitian ini adalah guru Bahasa Inggris yang mengajar di kelas X. Penelitian ini menggunakan rancangan enelitian kualitatif. Data diperoleh melalui kuesioner, wawancara, observasi, dan dokumentasi. Data dianalisis berdasarkan strategi pembelajaran Celce-Murcia (2001) dan Herrel dan Jordan (2004). Berdasarkan data analisis, penelitian ini menghasilkan beberapa temuan. Pertama, terdapat tiga puluh empat strategi pembelajaran yang telah digunakan oleh guru Bahasa Inggris di SMK Negeri di Singaraja, yaitu: Academic language Scaffolding, Advance organizers, Language focus lessons, Cloze, Collaborative reading, Communication games, Cooperative learning, Emotive writing tasks, Guided writing, Imaging, Interactive listening, Attribute charting, Language framework planning, Learning centers, Leveled questions, Listening and answering, Listening and repeating, Modeled talk, Multimedia presentations, Part-centered, Partner work, Peer Tutoring, Practical writing tasks, Predictable routines and signals, Realia strategies, Scripting, Socio-psycholinguistic, Sorting activities, Task listening, Visual scaffolding, Vocabulary processing, Vocabulary role play, Talk show, and Syntax surgery. Kedua, terdapat strategi yang sama yang digunakan di ketiga sekolah tersebut dengan perbedaan pada skill yang difokuskan and prosedurnya. Terdapat juga perbedaan jumlah strategi yang digunakan yang disebabkan oleh factor siswa dan pengalaman guru. Ketiga, terdapat beberapa masalah yang dihadapi guru terkait dengan pelaksanaan strategi pembelejaran. Masalah-masalah tersebut berkaitan dengan siswa, khususnya level siswa, motivasi siswa, dan keberagaman siswa, guru, dalam hal kurangnya motivasi mengajar and kepribadian guru, dan fasilitas. Kata kunci: strategi pembelajaran, SMK Negeri